Government finance : economics of the public sector - Due, John F.; Friedlaender, Ann F. (Delhi : A.I.T.B.S. Publishers and Distributors, 2002)
Economics
Keywords: Public finance; Government; Budget systems; Taxation; Fiscal federalism